What Makes Organoids Good Models of Human Neurogenesis? - Yang, Qian; Hong, Yan; Zhao, Ting; Song, Hongjun; Ming, Guo-li (Frontiers in Neuroscience, 2022)
Human neurogenesis occurs mainly in embryonic, fetal, and neonatal stages and generates tremendously diverse neural cell types that constitute the human nervous system. Studies on human neurogenesis have been limited due to a lack of access to human embryonic and fetal tissues. Brain organoids derived from human pluripotent stem cells not only recapitulate major developmental processes during neurogenesis, but also exhibit human-specific features, thus providing an unprecedented opportunity to study human neurodevelopment. First, three-dimensional brain organoids resemble early human neurogenesis with diverse stem cell pools, including the presence of primate-enriched outer radial glia cells. Second, brain organoids recapitulate human neurogenesis at the cellular level, generating diverse neuronal cell types and forming stratified cortical layers. Third, brain organoids also capture gliogenesis with the presence of human-specific astrocytes. Fourth, combined with genome-editing technologies, brain organoids are promising models for investigating functions of human-specific genes at different stages of human neurogenesis. Finally, human organoids derived from patient iPSCs could recapitulate specific disease phenotypes, providing unique models for studying developmental brain disorders of genetic and environmental causes, and for mechanistic studies and drug screening. The aim of this review is to illustrate why brain organoids are good models to study various steps of human neurogenesis, with a focus on corticogenesis. We also discuss limitations of current brain organoid models and future improvements.